(untitled) (Economic and Political Thought, 2020)
The aim of the article is to analyse the economic aspects of the phenomenon considered. It is usually perceived in ethical and moral terms, and the conclusions drawn are superficial, aimed at showing symptoms. However, the analysis undertaken in the article is an attempt to identify the efficient causes. Everyone seems to acknowledge the obvious fact that accumulating wealth is inseparable from human nature and market economy mechanisms. This results in huge socio-economic inequalities, which are widely criticized. This is even more the case when inequalities result from fraud and tax evasion. Although the owners of great fortunes try to pacify the unfriendly or even hostile attitude towards them, including through charity, however, this does not fundamentally address the rising gap between incomes at national and global level among various socio-professional categories. Another very telling sign of economic egoism is the rise of protectionism in international trade in recent years. Fuelled by economic nationalism, it disorganizes global exchanges by breaking down supply chains, which are equally important for individual economies and the global economy. If you add to this other phenomena, such as the coronavirus epidemic, which reinforce even further the negative consequences of economic egoism, then we are faced with a gloomy picture of the future of the world economy. This should mobilize us even more in the fight against its negative manifestations.